Lexical (micro-)dialectology of Uzh Romani - Beníšek, Michael (Romano džaniben, 2020)
This article is a dialectological study of the vocabulary of local Romani varieties that are spoken in the territory of the former Uzh County in the present-day Slovak–Ukrainian borderland. Uzh Romani is presented as a heterogeneous dialect area consisting of two regions: the Western Uzh region in Slovakia and the Eastern Uzh region in Ukraine. The study shows that the whole area is lexically part of a dialect continuum of North Central Romani and specifically of its eastern macro-area, while it is also characterised by dialect-specific features. The main focus of the article is a description of the lexical variability within the Uzh area. The study argues that the major differences between the Western Uzh and Eastern Uzh regions are due to the influence of different contact languages on both sides of the border. Moreover, we can observe that the Eastern Uzh region is lexically more conservative than the Western Uzh region, although there are some lexically conservative varieties even in the Western Uzh region. Furthermore, the article discusses the lexical variation within both regions and mentions examples of isoglosses that cross the national border. By considering lexical archaisms, the study also addresses the dynamics of the vocabulary and gives examples of inherited words that have become either locally or generally obsolete or even extinct.